Strengthening Africa’s climate-smart agriculture and food systems through enhanced policy coherence and coordinated action - Chevallier, Romy (Informa UK Limited, 2023)
Africa’s climate, food and agricultural policy agendas are often fragmented and yet their integration is a key requirement for enhancing the continent’s resilience and development outcomes. This research article explores actions to strengthen and better align Africa’s climate adaptation and mitigation responses in the agricultural sector. These include recommendations to promote the coherence of Africa’s climate-smart agriculture policy frameworks at numerous levels; to strengthen broad-based stakeholder engagement and inclusion; to promote institutional coordination, monitoring, evaluation and learning; and importantly, to enhance policy implementation.